Genetic Variation and Antifungal Susceptibility Profile of Candida auris - Adrir, Mutia Syarifah; Setianingrum, Findra; Adawiyah, Robiatul; Hasyim, Ammar Abdurrahman; Rozaliyani, Anna (Jurnal Ilmu Kedokteran, 2025)
Candida auris is an invasive yeast that has spread worldwide since it was first identified in Japan in 2009. C.auris has spread through four genetic clades that emerged between 2008 and 2013 and caused nosocomial outbreaks. The mortality rates of C.auris infections vary significantly between regions, ranging from 30 to 60%. C.auris infections can cause fungemia, invasive candidiasis, and spread to various organs. C.auris has a defense mechanism against the innate immune response and virulence factors that are not fully understood. High thermal and salinity tolerance, excretion of protease enzymes, and the ability to form biofilms are the main virulence factors that influence the pathogenicity of C.auris. Due to limited facilities, the diagnosis of C.auris infections is still hampered in some countries. Accurate strain identification methods are essential to prevent the rapid spread of this pathogen. Molecular techniques, including PCR and sequencing of the D1/D2 region of 28s rDNA or internal transcribed spacer using specific primers, are recommended for faster and more accurate identification. Genetic analysis revealed single-nucleotide polymorphisms (SNPs) that differed between clades, especially in the nuclear and mitochondrial genomes. C.auris exhibits high resistance to fluconazole, amphotericin B, and echinocandins, with some strains being resistant to all three. Resistance mechanisms include ERG11 gene mutations, Erg11p overexpression, and efflux pump activity. The rise of multidrug-resistant strains and high genetic variation complicates infection management, requiring heightened attention to prevent further spread.